The effects of the psychiatric counter-reform on harm reduction policy in the field of alcohol and other drugs (Research, Society and Development, 2023)
This researh aims to analyze the effects of the psychiatric counter-reform in the harm reduction policy in the field of alcohol and other drugs based on the analysis of the theoretical framework on the subject, together with the perceptions found from the experience in a Psychosocial Care Center Center for Alcohol and Drugs, as a resident social worker at the Adult Mental Health Program at FEPECS/ESCS/SES-DF. This is a descriptive study, of the literary review type, together with the experience report in a CAPS AD, in which the consequences of the political setback in the psychiatric reform movement that impacted harm reduction strategies in the field of AD were analyzed. The methodology used for data collection was the selection of articles that addressed harm reduction, mental health and psychiatric reform in the political context, in addition to the use of records in a field diary of the period of practical experience in the scenario in question. The analyzes showed that the advancement of the conservative political agenda, linked to the moralization of care for users of psychoactive substances, invalidated strategies that had a comprehensive look at the mental health of these individuals, such as the harm reduction strategy.